Księgozbiór Biblioteki Polskiej w Rumunii w zbiorach Biblioteki Śląskiej (PDF 1,66 MB) (Książnica Śląska, 2025)
The article presents the history and book collection of the Polish Library in Romania founded by Julian Ksawery Łukaszewski, a physician and emigrant after the January Uprising. The Polish Libraryfunctioned in Romania in the years 1866–1892, then it was transferred to the Upper Silesian Literary Society in Bytom, later transformedinto the Society of Friends of Science in Silesia (TPNS). In 1934, theRomanian library together with the TPNS collection was transferred to the Library of the Silesian Parliament, but only a fragment of itwas catalogued and included in the book collection before the war.The article is accompanied by a catalog of copies of Romanian provenance, which after the war were included in the Protected Book Collections and were catalogued many years later.